Home food gardening in modern cities: advances, issues, and future perspectives - Xu, Jingcheng; Lin, Tingwei; Wang, Ying; Jiang, Weijie; Li, Qiang; Lu, Tao; Xiang, Yahui; Jiang, Jingyong; Yu, Hongjun (Frontiers in Sustainable Food Systems, 2024)
Against the backdrop of the unexpected COVID-19 epidemic, governments are facing significant challenges in mobilizing food resources, particularly fresh products. It is inevitable that there will be intermittent shortages of food during the pandemic. As a result, home food gardening has gained considerable attention from city residents and policymakers in modern cities. This is due to its potential to provide food during humanitarian emergencies and lockdown. Moreover, home food gardening is increasingly becoming a popular recreational activity in many countries, offering therapeutic benefits such as fostering social bonds through knowledge-sharing and fruit-sharing, improving mental and psychological well-being, promoting outdoor physical exercise, and strengthening the connection between humans and nature. This review provides a comprehensive summary of the latest advancements in home food gardening, including cultivated species, devices, technologies, and current issues. It also proposes perspectives based on current researches to serve as a reference for future research and development.